ANALISA FEMINISME DALAM PERSPEKTIF HUKUM STUDI KASUS: PERLINDUNGAN HUKUM TERHADAP PEREMPUAN SEBAGAI KORBAN TINDAK PIDANA PEMERKOSAAN DI LINGKUP HUKUM POLDA METRO JAYA - Andika Setyo Nugroho; Amsori (The Juris, 2022)
Legal protection on women as the victim of sexual violence is provided to look after the victim in which her human right was being violated, so that she could be treated with justice according to human right law. This study aisns to a nalyze legal protection effort on woman as the victim of sexual violence eithin polda metrojaya a uthority. This study uses empirical approach. It is a research method which uses empirical facts directly taken from human conducts. It can be taken verbally by interview, direct observation, as well as physical archives. This study found that the efforts given by polda metrojaya towards the victim is only limited to legal protection. The victim does not receive material or on material compensation. As polda metrojaya only has the authority to process and to follow-up report filed by the victim. During investigation, the victim experienced physical and psychological disorder, hence the inability to gave informations and details regarding the sexual violence report. Victim was also unable to recognize the perpetrator as it happened in a secluded and dark place. These conditions caused some obstacles for investigators to further process the report. As there was no other witness than the victim herself, therefore the head of female and children assistance unit (Kanit PPA) worked alongside DP3AP2KB Jakarta and UPTD PPA Polda Metro Jaya to assist and support the victim during the investigation process.